Haemophilia and Exercise - Souza, J. C.; Simoes, H. G.; Campbell, C.S. G; Pontes, F. L.; Boullosa, D. A.; Prestes, J. (International Journal of Sports Medicine, 2012)
One of the most important objectives of intervention programs for persons with haemophilia (PWH) is to improve their quality of life. Regular physical activity has been recommended as an adjunct to conventional treatment, with positive results in the prevention of joint problems and bleeding, in addition to the improvement in cardiovascular function, muscle strength, and body composition. The objective of the present review was to present the benefits of aerobic and resistance training programs in PWH, as well to discuss the best exercise dose-response in the different levels of disease severity. We considered randomized controlled trials, study cases and literature reviews from MEDLINE and Highwire databases. After a detailed analysis of the studies involving exercise for PWH, it can be concluded that this intervention elicits some benefits for physical fitness and blood coagulation mechanisms, suggesting the application of physical training as a non pharmacological treatment in association with conventional treatment. Adequate and periodized resistance training considering the disease severity, accompanied by physical education professionals could improve muscle strength, balance and proprioception. In addition, aerobic training could reduce the risks of obesity and several metabolic and cardiovascular diseases. Exercise can improve several outcomes of quality in PWH.
Keywords: resistance training; aerobic training; bleeding disorders